2012
DOI: 10.1038/npp.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Glucocorticoid Receptor Gene at rs41423247 Moderates the Effect of Prenatal Maternal Psychological Symptoms on Child Cortisol Reactivity and Behavior

Abstract: Prenatal maternal psychopathology affects child development, but some children seem more vulnerable than others. Genetic variance in hypothalamic-pituitary-adrenal axis genes may influence the effect of prenatal maternal psychological symptoms on child emotional and behavioral problems. This hypothesis was tested in the Generation R Study, a population-based cohort from fetal life onward. In total, 1727 children of Northern European descent and their mothers participated in this study and were genotyped for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
2
21
1
Order By: Relevance
“…At first sight this strongly supports our present findings. Interestingly, Velders et al (2012) reported in contrast to the findings by Van Rossum et al (2006) and our findings that the C allele in combination with maternal psychological symptoms predicts emotional problems of the children at age of three. Given that these authors also investigated an interaction effect between rs41423247 and environmental influences on psychological health of the unborn child in later life (here age three), this contrary finding is especially noteworthy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At first sight this strongly supports our present findings. Interestingly, Velders et al (2012) reported in contrast to the findings by Van Rossum et al (2006) and our findings that the C allele in combination with maternal psychological symptoms predicts emotional problems of the children at age of three. Given that these authors also investigated an interaction effect between rs41423247 and environmental influences on psychological health of the unborn child in later life (here age three), this contrary finding is especially noteworthy.…”
Section: Discussioncontrasting
confidence: 99%
“…There are several limitations to the present study: First of all, recent results by Velders et al (2012) yielded evidence that in the unborn child, rs41423247 interacts with maternal psychological health on emotional behavior and cortisol reactivity of the then born child at the age of three. At first sight this strongly supports our present findings.…”
Section: Discussionmentioning
confidence: 78%
“…Studies also identify the glucocorticoid receptor variants as moderators of stress reactivity and of developmental outcomes to environmental adversity (Kumsta et al, 2007; DeRijk et al, 2008; Bet et al, 2009; Kumsta et al, 2009; Manenschijn et al, 2009; van West et al, 2010; Velders et al, 2012). Based on this evidence, we hypothesized that glucocorticoid receptor variants would differentiate individuals with a “for better and for worse” sensitivity to environmental exposure (Belsky & Pluess, 2009), characterized by reduced rates of externalizing psychopathology in response to intervention and elevated rates in the absence of intervention.…”
Section: Introductionmentioning
confidence: 99%
“…At the level of psychopathology, NR3C1 variants are associated with child-onset mood disorder (Mill et al, 2009), adolescent alcohol abuse (Desrivieres et al, 2011), and adult major depression (van Rossum et al, 2006; van West et al, 2006; Zobel et al, 2008). NR3C1 variants have also been associated with differential response to environmental exposure, including greater incidence of depression among individuals exposed to adversity (Bet et al, 2009) and irregular cortisol reactivity and behavior problems among the offspring of mothers with prenatal psychological symptoms (Velders et al, 2012). …”
Section: Introductionmentioning
confidence: 99%